AJARAN TAREKAT SYEKH AHMAD AT-TIJANI : ANALISIS TUJUAN DAKWAH - Choiriyah Choiriyah (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2014)
Congregation (tarekat) is an institution that was born as a medium for the servant of God who wants to achieve closeness with Allah and His Messenger, as well as Tijaniyyah. In Tijaniyyah to achieve these objectives Sheikh Ahmad at-Tijani as founder Tijaniyyah teach three forms of remembrance, the remembrance lazimah, Hailalah and wadzifah. Dakwah material contained in remembrance remembrance is to invite people to a certain character to God to ask for forgiveness istighfar repent to Allah SWT. Invite to reproduce read Sholawat to the Prophet Muhammad and materials related to faithful of some one.